Born to swing : Lil Hardin Armstrong's life in jazz - Rockliff, Mara (Calkins Creek, an imprint of Highlights, 2018)
Ever since she was a young girl, Lil Hardin played music with a beat. She jammed at home, at church, and even at her first job in a music store. At a time when women's only place in jazz was at the microphone, Lil earned a spot playing piano in Chicago's hottest band.